Psychological Wellbeing and Grit among Management Graduates in India: Understanding the Moderating Role of Knowledge of Strengths - Chakraborty, Tanusree; Chatterjee, Bipasha; Mishra, Nandita; Tripathi, Malabika (International Journal of Psychosocial Rehabilitation, 2020)
Psychological grit predicts success in a range of circumstances, such as greater probability of having lifelong academic achievement and success at jobs. In the interests of including the fullest picture of how grit relates to well-being, knowledge on an individual’s strength has been considered to be a possible mediator. The present study aims to understand the nature of psychological wellbeing and grit among young managers who have just been placed at various companies after completing management education, and how their knowledge strength have moderated their sense of psychological wellbeing and grit. For the purpose, 450 students of VI Trimester of their management course were employed as respondents who have already been placed in various companies and are ready to join their jobs within two months from the date of data collection. The study has found that, psychological wellbeing impacts grit and knowledge of own strengths and use of those have moderating effect on psychological wellbeing and grit. Grit entails working strenuously in difficult situations, maintaining effort and concentration over years despite being unsuccessful sometime.